The interaction between sporting footwear and natural playing surfaces: an overview - Barry, E. B.; Milburn, P. D. (Proceedings of the First Australasian Biomechanics Conference, 1996, Sydney, 1996)
This paper presents an overview of a programme of research into the frictional and torsional properties of the footwear/surface interaction. The overview will conclude with two main research themes: (a) Surface - footwear interaction, involving engineering, tribology and soil mechanics emphases; and (b) Leg - footwear interaction, involving a biomechanical emphasis.